Correlation of dental and chronological maturity in girls and boys aged 7 to 14 years - Nikolić Zorana; Šćepan Ivana; Marković Evgenija (Serbian Medical Society - Dental Section, Belgrade, 2005)
The aim of the study was to assess correlation level of dental and chronological maturity related to gender in a group of children of our population. Material and method: Total number of 320 girls and boys, 7 to 14 years old, participated in the study. Dental age assessed by Demirjian's method. Statistical data were analyzed by mean value and SD for dental maturity in age groups of 7, 8, 9, 10, 11, 12, 13 and 14 years for girls and boys, respectively. Calculating the equation of linear regression and the determination and correlation ratio assessed correlation level of dental and chronological age. Results and conclusion: According to the results obtained, it can be concluded that mean values of dental age are coinciding with the chronological maturity in all 8 age groups which is confirmed by high interdependence of dental and chronological maturity (78.6% for boys and 79.6% for girls). .